Pengaruh Pertumbuhan Aset, Struktur Modal dan Cash Flow Operating terhadap Nilai Perusahaan yang Terdaftar Bursa Efek Indonesia Periode 2021-2024 - Napitu, Ulul Azmi; Giyartiningrum, Eko (Jurnal Ragam Pengabdian, 2026)
This study examines firm value dynamics in the industrial sector listed on the Indonesia Stock Exchange (IDX) during 2021–2024 by analyzing the effects of asset growth, capital structure, and operating cash flow. A quantitative explanatory approach was applied using secondary data from the annual reports of 16 companies selected through purposive sampling. Data were analyzed using panel data regression with EViews 13, and the Fixed Effect Model (FEM) was identified as the most appropriate model based on the Hausman test. The results show that, partially, asset growth and operating cash flow do not have a significant effect on firm value. This indicates that asset expansion without productivity improvement and operating cash flow that is not effectively allocated to high-return investments are insufficient to enhance firm value. In contrast, capital structure has a positive and significant effect, highlighting the importance of financing decisions in value creation. Simultaneously, all variables significantly influence firm value, with an adjusted R-squared of 0.544, indicating moderate explanatory power. This suggests that other factors such as corporate governance and macroeconomic conditions may also affect firm value.